PROGRAM ASN BERDAYA KABUPATEN JEPARA: BUDIDAYA CABAI PEKARANGAN UNTUK KETAHANAN EKONOMI KELUARGA - Diva Nadia Aprisya; Ersa Naila Sari; Muh Fakhrihun Na’am (LPPI UMN AL WASHLIYAH, 2026)
The Civil Servant Empowerment Program in Jepara Regency was initiated in response to fluctuations in chili prices, which have led to increased household expenses for civil servants. This study aims to analyze the program’s ef ectiveness in promoting family economic self-reliance through chili cultivation in home gardens. The method used is a qualitative descriptive approach with data collection techniques consisting of observation, interviews, and documentation. The results of the study indicate that this program is capable of improving civil servants’ knowledge and skills in chili cultivation, as well as encouraging the productive use of backyard land. Additionally, the program has proven to help reduce household expenses and provide additional income opportunities from the harvest. Factors contributing to the program’s success include technical assistance, the availability of production resources, and active participant engagement. However, several challenges exist, such as civil servants’ limited time and the impact of weather conditions on crop yields. Overall, the program is deemed ef ective in strengthening the economic resilience of civil servants’ families and holds potential for broader implementation in other regions.